2010
DOI: 10.1007/s10482-010-9423-7
|View full text |Cite
|
Sign up to set email alerts
|

16SrRNA and enzymatic diversity of culturable bacteria from the sediments of oxygen minimum zone in the Arabian Sea

Abstract: Sediment underlying the oxygen minimum zone of the eastern Arabian Sea is rich in organic matter. Bacteria in this sediment-water interface are of great ecological importance as they are responsible for decomposing, mineralizing and subsequent recycling of organic matter. This study has for the first time addressed the phylogenetic and functional description of culturable bacteria of this region. Genotypic characterization of the isolates using amplified rDNA restriction analysis (ARDRA) followed by 16SrRNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 66 publications
2
29
1
Order By: Relevance
“…Previous studies have also reported production of different hydrolases from marine bacteria belonging to genera Erwinia, Vibrio, Psychrobacter marinobacter, Chromohalobacter, Halomonas, Microbulbifer, and Alteromonas (Dalmaso et al, 2015), whereas the production of enzymes by marine Aidingimonas have not been previously reported. The second dominant phylum Firmicutes comprised of Bacillus, which has been reported as a dominant genus among all the marine enzyme-producing bacteria (Divya et al, 2010). This is because Bacillus is easy to culture and can endure harsh environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported production of different hydrolases from marine bacteria belonging to genera Erwinia, Vibrio, Psychrobacter marinobacter, Chromohalobacter, Halomonas, Microbulbifer, and Alteromonas (Dalmaso et al, 2015), whereas the production of enzymes by marine Aidingimonas have not been previously reported. The second dominant phylum Firmicutes comprised of Bacillus, which has been reported as a dominant genus among all the marine enzyme-producing bacteria (Divya et al, 2010). This is because Bacillus is easy to culture and can endure harsh environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At 90% similarity level, thermotolerant isolates from Bakreshwar, Balrampur, Chumathang and Vashist thermal springs grouped into 14, 14, 11 and 9 clusters respectively. ARDRA has been effectively utilized in the past for both culture dependent and culture independent diversity studies as a tool to group the isolates and clones into phylotypes [17][18][19].…”
Section: Amplified Rdna Restriction Analysismentioning
confidence: 99%
“…The use of 16S rRNA gene sequencing in combination with ARDRA for grouping into phylogenetic clusters and identification of bacteria is well documented [18][19][20]. Although the number of phylogenetic clusters is less in Vashist, the average bacterial population was highest in Vashist and the lowest in Balrampur.…”
Section: S Rrna Gene Sequencing and Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…OMZ alters the chemical composition of the surrounding environment and also induce stress on the organisms (Childress and Sieibel 1998; Schneider and Bush-Brown 2003). Previous studies on OMZ have concentrated primarily on the diversity of microorganisms in these waters/sediments (Bryant et al 2012; Divya et al 2010, 2011) and their functional role in nitrogen cycle (Paulmier and Ruiz-Pino 2009). Though OMZ constitute only about 0.1% of the total oceanic volume, about 30–40% of the total oceanic nitrogen loss is estimated to occur within it.…”
Section: Introductionmentioning
confidence: 99%